Fintech and financial inclusion: the cases of Mexico, Chile, and Peru - Ignacio Esteban Carballo; Facundo Dalle-Nogare (Revista CEA, 2019)
This work addresses financial technology (Fintech) and its relevance in contexts of promotion of financial inclusion. For that purpose, a literature review was conducted using the most important terms that define those two fields, and microfinance was highlighted as the predecessor of financial inclusion. More specifically, the recent evolution (before 2018) of the cases of Chile, Mexico, and Peru was studied to conclude that, although important progress has been made in the three countries, the institutional framework is very different in each one of them, which results in dissimilar opportunities and challenges in every context. It is concluded that the channels that determine the relationship between Fintech and financial inclusion are wide ranging and heterogeneous. Policies that engage sustainable efforts by the public and private sector should be promoted to support financial inclusion processes adapted to new technologies. Overall, this work sheds light on the digitalization processes financial services are undergoing as well as their heterogeneity.